Computer-based instrumentation for pressure instrument using visual basic application - Mohd Aizat Faiz, Mohd Yazid (2008)
Generally, the project is about the implementation Graphical User Interface (GUI) of Visual Basic on pressure measurement. The focus on my project is to develop an interface of instrumentation systems for pressure measurement and to integrate the pressure transmitter to software system. This project can be separated into 2 parts which are software and hardware. Using Visual Basic 2008 as software, I develop the GUI so that it can be used for academic purpose especially in laboratory for BEE 4632 Industrial instrumentation subject. This software can be integrated with pressure transmitter using DAQ Board. In my case, I used Advantech USB-47I6 DAQ Boards because it used USB port as connector from instrument to computer. This DAQ Board is easy to use because it comes with installation for plug and play function, English version manual and Device Manager. For instrument, I used Differential Pressure Transmitter. User needs to key in minimum and maximum MSU applied and minimum and maximum Desired UUT in Data Page tab before further to get the actual UUT. After run 3 times of experiment and completing the table, user can calculate the average and output error. Then they can continue to get an average and output error percentage curve in Graph Page tab. Implementation of GUI to this instrumentation system can help to increase the efficiency in calculating the output data.